Effects of varying concentration of soybean oils on hemato-biochemical profile in mice (Bangladesh Journal of Animal Science, 2013)
Plant fat like soybean oil is believed to be less harmful to our body compared to animal fat. To know the effect of soybean oil on hemato-biochemical profile, a total of 20, 6 weeks old Swiss Albino mice were randomly divided into 4 equal groups (n=5). Group A was considered as control fed with rat pellets and others were treated with 2% (group B), 4% (group C) and 8% (group D) soybean oil, respectively, in addition to pellets. At the end of 45 days, hemato-biochemical parameters were analyzed. The total erythrocyte count (TEC) and hemoglobin (Hb) content were increased significantly (P